Second Language Learning Strategy for Young Learners: Learning Hiragana as A Process in Japanese Language Acquisition - Mardani, Desak Made Sri; Widodo, Pratomo; Andriyanti, Erna; Suartini, Ni Nengah (Makassar State University, 2024)
Abstract. Learning strategies in the Japanese language for young learners tend to be applied to children in Japanese mixed-married families or foreign children in Japan. However, this study tried to apply a learning strategy for a young learner who does not have a background in the Japanese environment or experience with Japanese people and culture. This study aims to describe a learning strategy by applying mnemonics to young learners in Japanese language acquisition, particularly in the Japanese character Hiragana. This research used qualitative descriptive design, with research instruments that include researchers, observation forms, and literature sources. The data collected in this study were analyzed using an interpretive approach. This study used a mnemonics-based digital tool application was used to assist the young learner in learning the Japanese character, Hiragana. This study shows that mnemonics can improve young learners' Hiragana acquisition. Learning strategy by applying mnemonics helps the young learner memorize each character and improves associative skills and Japanese vocabulary as a language acquisition process. Some characters are similar and confusing for beginners, and some Japanese characters do not exist in Indonesian, which makes it difficult for learners to pronounce them. The application greatly helps the subject memorize each character and improves associative skills and Japanese vocabulary as a language acquisition process. Through continuous reading practice, the subject can distinguish almost similar characters and help pronounce vocabulary. This application is very effective for parents who want to introduce Hiragana characters to young learners, with intensive reading practice and creating an environment that uses Hiragana.Keywords: learning strategy, mnemonics, Hiragana, young learner, language acquisition